2019
DOI: 10.1021/jacs.8b13182
|View full text |Cite
|
Sign up to set email alerts
|

Ketones and Aldehydes asO-Nucleophiles in Iridium-Catalyzed Intramolecular Asymmetric Allylic Substitution Reaction

Abstract: Ketones and aldehydes are employed as enol O-nucleophiles in an iridium-catalyzed asymmetric allylic substitution reaction. The reaction proceeds well in the presence of a well-defined chiral iridium complex under mild conditions. A series of chiral 2H-1,4-oxazine skeletons can be obtained in up to 94% yield with 99% ee. The utility of this novel method has been demonstrated by its implementation in the first enantioselective synthesis of (+)-chelonin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…Because of their enamine character and the potential instability of the unsaturated deprotected amine intermediate, we first explored double bond reduction. When compound 23 was subjected to classical reduction methods, no reduction was observed (Pt/C or Pd/C, H 2 (50 bars); Pd(OAc) 2 , XantPhos, HCOOH, 90 °C) If a first attempt at ionic reduction with triethylsilane/ trifluoroacetic acid [12] was unsuccessful (Table 4, entry 1), we found that increasing the triethylsilane to 22.0 equiv. in a mixture of TFA/DCM (50/50) gave successful reduction with no amine deprotection.…”
Section: Updatesmentioning
confidence: 99%
“…Because of their enamine character and the potential instability of the unsaturated deprotected amine intermediate, we first explored double bond reduction. When compound 23 was subjected to classical reduction methods, no reduction was observed (Pt/C or Pd/C, H 2 (50 bars); Pd(OAc) 2 , XantPhos, HCOOH, 90 °C) If a first attempt at ionic reduction with triethylsilane/ trifluoroacetic acid [12] was unsuccessful (Table 4, entry 1), we found that increasing the triethylsilane to 22.0 equiv. in a mixture of TFA/DCM (50/50) gave successful reduction with no amine deprotection.…”
Section: Updatesmentioning
confidence: 99%
“…Ionic conditions were then tried, and while the use of triethylsilane/trifluoroacetic acid failed with compound 5, they proved to be successful starting from spirocycle 9. 33 The desired spiromorpholinone 41 was isolated in 84% yield.…”
Section: Scheme 2 Oxazoline Formationmentioning
confidence: 99%
“…However, methodologies for the enantioselective synthesis of cyclic oxime ethers relying on transition-metal-catalyzed allylic substitution remain undeveloped. The groups of Du and Takemoto have reported enantioselective intermolecular O -allylation reactions to access acyclic oxime ethers using palladium and iridium catalysts, respectively. In 2019, You and co-workers documented a single example of the intramolecular iridium-catalyzed O -allylation of an oxime, which furnished a seven-membered 1,2,5-oxadiazepane product . Yet, a general enantioselective method that provides access to cyclic oxime ethers of various ring sizes remains elusive.…”
mentioning
confidence: 99%
“…In 2019, You and co-workers documented a single example of the intramolecular iridium-catalyzed O-allylation of an oxime, which furnished a seven-membered 1,2,5-oxadiazepane product. 10 Yet, a general enantioselective method that provides access to cyclic oxime ethers of various ring sizes remains elusive.…”
mentioning
confidence: 99%